Penyuluhan Hukum tentang Hukum E-Commerce dan Digital Marketing di Era Perkembangan Dunia Siber - Dirga Agung; Andi Dewi Pratiwi; Lidwina Apriliana Allo Tangko (Beru'-beru': Jurnal Pengabdian kepada Masyarakat, 2025)
Community service activities carried out by Dr. Dirga Agung, S.H., M.H. which was carried out in mid-May from 13 to 14 May 2025, took place in the Omorfoshop Shop Meeting Room in Makassar City and Gowa Regency. Counseling on E-Commerce Law and Digital Marketing of Skincare Shops in Makassar City and Gowa which was carried out is one way to provide an understanding of E-Commerce Law and Digital Marketing, so it is hoped that this legal counseling can be used as a step to increase legal awareness and provide an understanding of the various types of criminal modus operandi in the world of e-commerce and digital marketing in the Makassar City and Gowa Regency areas. As recently there has been a lot of news about the increasing cases of cybercrime, especially in the fields of e-commerce and digital marketing which are problems that are still an important concern in the world of criminal law, On a wider scale, many producers and consumers in big cities in Indonesia are both perpetrators and victims of criminal acts that use e-commerce as a means and purpose of various types of crimes. In addition, the lack of public attention to the dangers and risks of crime in the world of e-commerce and digital marketing among the public and business actors is the main cause of the increase in criminal acts in cyberspace, especially in the e-commerce sector.